Learning Resources: Nature, Types, Selection, and Utilization of Learning Resources - Yasin, Nur Ali; Hasanah, Raudlatul; Hakim, Abdul (Journal of Advance in Language, Literature, and Education, 2025)
Learning is a lifelong and multifaceted process shaped by the dynamic interaction between individuals and their surrounding environment. Within this process, learning resources serve a crucial function in helping to achieve educational objectives. However, in actual educational settings, these resources are often underutilized. This study employs a descriptive qualitative approach using a library research method, which involves examining various relevant sources and literature related to learning resources in educational contexts. The findings reveal that learning resources encompass all elements that can support learning, including people, environments, media, and technological tools. The selection of appropriate learning resources should align with learners’ characteristics, instructional goals, and the suitability of content. This study highlights the vital role of educators in carefully selecting and utilizing learning resources to enhance the overall effectiveness of the learning experience.